Effect of Electrical Stimulation Conditions on Neural Stem Cells Differentiation on Cross-Linked PEDOT:PSS Films - Sordini, Laura; Garrudo, Fábio F. F.; Rodrigues, Carlos A. V.; Linhardt, Robert J.; Cabral, Joaquim M. S.; Ferreira, Frederico Castelo; Morgado, Jorge (Frontiers in Bioengineering and Biotechnology, 2021)
The ability to culture and differentiate neural stem cells (NSCs) to generate functional neural populations is attracting increasing attention due to its potential to enable cell-therapies to treat neurodegenerative diseases. Recent studies have shown that electrical stimulation improves neuronal differentiation in stem cells populations, highlighting the importance of the development of electroconductive biocompatible materials for NSC culture and differentiation for tissue engineering and regenerative medicine. Here, we report the use of the conjugated polymer poly (3,4-ethylenedioxythiophene) doped with polystyrene sulfonate (PEDOT:PSS CLEVIOS P AI 4083) for the manufacture of conductive substrates. Two different protocols, using different cross-linkers (3‐glycidyloxypropyl)trimethoxysilane, GOPS and divinyl sulfone, DVS) were tested to enhance their stability in aqueous environments. Both cross-linking treatments influence PEDOT:PSS properties, namely conductivity and contact angle. However, only GOPS-cross-linked films demonstrated to be stable during their incubation in water for 15 days. GOPS-cross-linked films were used to culture ReNcell-VM under different electrical stimulation conditions (AC, DC and pulsed DC electrical fields). The polymeric substrates exhibit adequate physicochemical properties to promote cell adhesion and growth, as assessed by Alamar Blue® assay, both with and without the application of electric fields. NSCs differentiation was studied by immunofluorescence and quantitative real-time polymerase chain reaction. This study demonstrates that the pulsed DC stimulation (1 V/cm for 12 days), is the most efficient at enhancing the differentiation of NSCs into neurons.